The Divulgation of Science in the 21st Century - Morales Salas, Rubí Estela (Emerging Trends in Education, 2021)
Science is the product of human efforts to systematize knowledge and it dates back to prehistoric times, when Neolithic civilizations needed to solve everyday questions that helped improve their quality of life. With the passage of time it was not enough to systematize knowledge, but it was necessary to communicate and disseminate it. This communication exposes the evolution of the divulgation of science and the needs it has in the 21st century when making use of ICT. It is concluded that science’s divulgation goes beyond just communicating but must be feasible to penetrate the understanding of the general public so that social reality can be transformed, supporting these actions through the use and application of the power derived from ICT.